Marx, Gandhi and Socialism - Lohia, Rammanohar (Hyderabad, 1963)
Truth is known from an aspect or an angle. That is not to say that truth is partial. In fact, partial truth is strictly speaking an error of expression. Truth is either whole or not at all. What is perhaps loosely meant by this frequent idiom of partial truth is not the denial of whole truth but assertion of aspectual truth or truth from an angle. All truth is discovered from the aspect or the angle which the seeker or the knower adopts. Error may lie in not taking up the angle properly. Or, even if a proper aspect or stance were adopted, error may arise from hurried, blocked or careless view. Results of such error are sometimes described as relative truth, when not a lie. What turns a relative truth into a lie is a blatant error of aspect or viewing or their cru dity in relation to complexities of life. A more sophisticated and re fined aspect were needed, or a longer and more detailed or unpreju diced viewing. Relative truth and partial truth are fallacious modes of expression, which convey the profound truth that all truth derives from an angle, a sight or a line of vision. When the sight has not been properly set or the viewing done, lie alone may not ensue, well might it be relative or partial truth.
Keywords: Gandhi, M .K